TINGKAT PENCEMARAN LOGAM Pb DAN Zn PADA PERAIRAN SELAT AIR HITAM DENGAN BIOMONITOR SIPUT Cerithidea obtusa - Bahtiar Denny Edison; Yusni Ikhwan Siregar; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2015)
ABSTRACTThis study aimed to analyze the content of Pb and Zn in sea water, sediment and Cerithidea obtusa and the feasibility of consumption of C. obtusa. This study was conducted from October to December 2014 with the location of the survey is the Selat Air Hitam of Meranti Islands regency of Riau Province. The results showed that the Pb content of sea water ranges from 91.909 to 94.606 μg/l, sediment ranged from 5.125 to 5.705 μg/g and C. obtusa ranged from 6.732 to 6.784 μg/g. Zn content of sea water ranges from 400 to 445.349 μg/l, sediment ranged from 25.174 to 27.035 μg/g and C. obtusa ranged from 32.267 to 36.105 μg/g. The analysis showed that the average content of Pb and Zn in the sediment is still far below the standard value of ERL and ERM, which means not giving a real biological effect on the organism. PLI standard shows the condition of a low level of contamination that has not been necessary remedial action. The average content of Pb and Zn of C. obtusa still below the Directorate General Quality Standard of POM so it is still feasible and safe for public consumption. The PTWI value as the limit consumption of C. obtusa is 1.04 kg/70 kg body weight/week for Pb and 28.67 kg/70 kg body weight/week for Zn.